Pandemics and Human Capital: Panel Data Evidence From 122 Countries - Sun, Jianmin; Cai, Kaihao; Shen, Hongzhou (Frontiers in Public Health, 2022)
This study investigates the determinants of human capital stocks, measured by the Penn World Table data, in the panel dataset of 122 countries from 1996 to 2019. The special role is given to the World Pandemics Uncertainty index to measure pandemics uncertainty across countries. The paper finds that per capita gross domestic product and population increase human capital stocks. The decline in fertility rates leads to a higher level of human capital. The interesting evidence is that pandemics' uncertainty decreases human capital. These findings are valid when we focus on both the high-income and the middle/low-income economies. These results are against the Becker-Lewis theory's validity since sources of uncertainty are negatively related to human capital.